What digital technology do early childhood educators use and what digital resources do they seek?. Issue 1 (March 2019) - Dwyer, Anne; Jones, Caroline; Rosas, Lee
Continuing professional learning is vital to early childhood professionals, and the use of digital technology can potentially reduce costs and improve access. In this study, 74 educators across 17 early childhood services in Australian urban and regional locations completed a questionnaire about their personal and professional uses of digital technology to find resources. The results indicate most early childhood educators use digital technology to construct their own professional knowledge bases, and though they make some use of formal resources around national standards, they make greater use of informal resources and discussion groups. They tend to seek practical information and activity ideas and ways to connect with other professionals, although this varies somewhat by years of professional experience, age and the socioeconomic context they work in. Results highlight early childhood educators' professional learning desires and the potential value of mobile learning for providing access to professional learning for early childhood educators working in resource-limited and geographically limited settings.